Geographical distribution of product development capabilities in the automobile industry: towards a hierarchical division of labour in Mercosur - Obaya, Martín (2014)
In the last decade, some carmakers with operations in Mercosur delegated a growing number of product development responsibilities to their subsidiaries operating in Argentina and Brazil. As a result, these subsidiaries were able to accumulate capabilities that allowed them to introduce innovations of increasing complexity into the vehicles manufactured in the region. Empirical evidence suggests that, beyond the differences observed in the strategies adopted by carmakers in Mercosur, the most intense capability accumulation experiences were largely concentrated in subsidiaries located in the Brazilian territory. As a result, a hierarchical division of labour has progressively taken shape within Mercosur favouring the subsidiaries located in this country, at the expense of their Argentinian counterparts. Through the examination of three companies, this article aims to analyse the process of accumulation of product development capabilities in subsidiaries operating in Argentina and Brazil between 1991 and 2011.